Cerebrospinal Fluid Involvement in a Case of Visceral Leishmaniasis Associated with Hemophagocytic Lymphohistiocytosis - Mahmoud Fathalla; Javad Hashim; Hussein Alkindy; Yasser Wali (Sultan Qaboos University Medical Journal, 2007)
Hemophagocytic Lymphohistiocytosis (HLH) implies a benign generalized histiocytic proliferate with erythrophagocytosis and it includes familial hemophagocytic lymphohistiocytosis and secondary hemophgocytosis. Spinal fluid changes like mild to moderate pleocytosis (most of the cells are lymphocytes and macrophages) and sometimes hemophagocytosis are seen in primary HLH but are not reported in secondary HLH. Here we report a case of a previously healthy 10 months old male infant who was diagnosed as familial HLH with evidence of CSF hemophagocytosis. He was started on the HLH 2004 treatment protocol with no improvement. A second bone marrow aspiration revealed leshmania donovani antibodies and he was started on anti-leishmania treatment with dramatic response.To the best of our knowledge, this is the first case of secondary HLH with evidence of hemophagocytosis in cerebrospinal fluid.